Analisis Learning Obstacles Pada Materi Simetri Lipat dan Simetri Putar Untuk Kelas III Sekolah Dasar - Candra Putri Kirana Nurvita; Ryky Mandar Sary; Filia Prima Artharina (STKIP Andi Matappa Pangkep, 2022)
This study aims to analyze the types and causes of learning obstacles experienced by elementary school class students on the material of folding symmetry and rotational symmetry. The approach used is a qualitative approach with descriptive research methods. Data collection techniques used in this study were tests, interviews, observation, and documentation. The results showed that there were three learning obstacle factors experienced by the third grade on the material of folding symmetry and rotational symmetry, namely 77% of students experienced ontogenical obstacles, 81% of students experienced didactical obstacles, and 100% of students experienced epistemological obstacles. The cause of students experiencing ontogenical obstacles is the lack of student interest in participating in learning, lack of readiness to accept learning, both psychological and material readiness. The learning presented by the teacher is too difficult and the students do not understand the prerequisite material. The causes of students experiencing didactical obstacie are due to the lack of teacher readiness in the learning process, limited material delivery, and the teacher does not provide practice questions. The cause of students experiencing epistemological obstacles is because the teacher does not give non-routine questions and there is a jump in the prerequisite material.